Comparative assessment of SAS, IDDES and hybrid filtering RANS/LES models based on second-moment closure. (June 2021) - Wang, Guangxue; Wang, Shengye; Li, Hao; Fu, Xiang; Liu, Wei
The question of which turbulence model is better for a given class of applications is always confusing for the CFD researchers and users. Comparative assessments of scale-adaptive simulation (SAS), improved delay detached-eddy simulation (IDDES) and other hybrid RANS/LES models based on eddy-viscosity models (EVMs) are thoroughly investigated. But how well they perform based on a second-moment closure needs to be answered. In this paper, a widely acclaimed Reynolds-stress model (RSM) in aeronautical engineering, SSG/LRR-ω model, is carried out. The relevant test cases include the NACA0012 airfoil stalled flows and turret separated flow. In order to make a more reasonable comparison, a seventh-order scheme WCNS-E8T7 is adopted to reduce the influence of the numerical dissipation and a symmetrical conservative metric method is used to ensure the robustness. By comparing with the relevant experimental data and the solutions by original SSG/LRR-ω model (etc. URANS), it shows that all of the three hybrid methods (SAS, IDDES and hybrid filtering methods) based on the SSG/LRR-ω model have a good ability to simulate unsteady turbulence. Among them, the IDDES correction has the most potential.